Not The Nineveh, But Jonah: Exploring God’s Mercy in The Book of Jonah - Sia Kok Sin (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Many scholars argue that the book of Jonah is about God’s mercy for Nineveh. However, I argue that the focus of this book is God’s mercy for Jonah, the stubborn, disobedient, and reluctant prophet. We can find that indeed God’s mercy was for Nineveh by relenting his judgment to the repented Nineveh, but it was not the focus of God in this book. If the focus is the Nineveh, the book of Jonah could end with chapter three which states God relented his judgment on the Nineveh. This study was conducted with narrative method to the whole narrative of the book of Jonah. This study showed that from chapter one to chapter four, God dealt mercifully to Jonah who had to deal with his struggles as God’s prophet. We can see how God dealt mercifully with Jonah through this book. I conclude that a narrative reading of the entire narrative of the book of Jonah can produce a different interpretation from the existing one.